2021
DOI: 10.37373/tekno.v8i1.74
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kegagalan Rem Hino Fg 235 Dengan Menggunakan Metode Fishbone Analisis

Abstract: Berawal dari tekanan angin yang cepat habis atau rendah, ketika dilakukan pengereman berkali-kali pada saat jalan padat merayap. Tujuan dari penelitian untuk mengetahui kegagalan proses pengereman, agar tidak terulang kembali. Adapun metode dalam penelitian ini menggunakan fishbone analysis. Dari hasil penelitian kecelakaan truk yang sering terjadi kegagalan pengereman yang disebabkan oleh tekanan angin rendah, adanya gelembung udara pada minyak rem, muatan berlebih, dan disebabkan kurang pengetahuan pengemudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…PA = š‘„100% = 95,71% The HD 1500-7 dump truck unit's maintenance performance is calculated in Figure 2 when the standby condition is oil entering through the hydraulic oil inlet (2) and when the auto lube system is running the controller or timer sends a signal to the solenoid valve (3) to open the hydraulic oil line from (2) to the reciprocating pump (7) which passes through the reducing valve (4), oil pressure gauge (5) and flow control valve (6). In addition, there is hydraulic oil that goes to the vent valve (11) through the orifice (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PA = š‘„100% = 95,71% The HD 1500-7 dump truck unit's maintenance performance is calculated in Figure 2 when the standby condition is oil entering through the hydraulic oil inlet (2) and when the auto lube system is running the controller or timer sends a signal to the solenoid valve (3) to open the hydraulic oil line from (2) to the reciprocating pump (7) which passes through the reducing valve (4), oil pressure gauge (5) and flow control valve (6). In addition, there is hydraulic oil that goes to the vent valve (11) through the orifice (12).…”
Section: Resultsmentioning
confidence: 99%
“…Grease is the lubricant employed in this system because it can enter the spaces between the linkage group components [2]. The automatic lubrication system, also known as the Auto lube system, is utilized in the Dump Truck HD 1500-7 unit's lubrication system [3]. Regular maintenance is required for the Auto lube system, especially regarding the grease level in the grease tank and the pressure of the grease coming from the electric grease pump [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by (Sugiharjo and Wilarso, 2021) using the fishbone analysis method concluded that a lack of grip on the brakes and insufficient air pressure caused the failure of the braking process. One of the causes of high air consumption is the discovery of brake lining gaps outside the manufacturer's standards.…”
Section: Literature Reviewmentioning
confidence: 99%